Strategi Pelayanan Calon Jemaah Haji Musim Pandemi - Yuningsih, Yuyun; Bagja, Haliza; Aulia, Burhanudin (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
Hajj is spiritual worship that requires a strong mental and physical and also a comprehensive understanding. Its implementation involves divine management and human management by paying attention to various government regulations and policies, including policies during the pandemic season. The strategy of serving prospective pilgrims during the pandemic season at the Ministry of Religion of the City of Bandung is the goal of this study. The research method used is the descriptive qualitative method. The data was taken using data collection techniques through observation and interviews with the organizers of the pilgrimage at the Ministry of Religion of the City of Bandung and prospective pilgrims under the auspices of KBIH and independent congregations. The study results revealed that the service strategy for prospective Hajj pilgrims in Bandung City was effective and professional, although with various alternatives. The scope of the service strategy includes services, development, and protection. Information services based on digital transformation, guidance for Hajj rituals carried out online with various platforms, and protection to build mental solid and psychologically healthy congregations in order to accept the reality of various Hajj policies in the pandemic season and provide confidence that pilgrims have the right to protection from the government.